Construction management in the era of BIM : automation of facade tracking system - Soh, Che Jui (Nanyang Technological University, 2020)
This project presents an industry case study which I had encountered during my professional attachment in enhancing the utilisation of BIM data in project management within the Main Contractor’s organisation. The main problem that faced by Main Contractor during the professional attachment is the separation of BIM data and RFID tracking system adopted in the façade progress monitoring system. This report explored the practicability of using existing tools to improve the utilisation of data in BIM environment within RFID progress tracking system. During the development of the solution, the gaps in the information flow between the BIM database and RFID tracking data have been identified and this project mainly focused on the possibilities to bridge the gaps. Throughout this project, we found that Dynamo and C# Programming Language are some of the useful tools to plug these gaps. In our solutions, we make use of an Excel file, called “Linking file” to collect input data from BIM database and RFID data to manipulate the façade tracking process within BIM environment. We have also discussed on reason using such approach instead of direct link. From this study, we believed that one of the keys in levelling up the construction automation is to develop civil engineer with deep knowledge in both civil engineering and BIM technologies, to bridge the gaps between the user and the technology. With this, we strongly believe that the digitalisation and automation of the construction industry will be greatly lifted and improved in near future.